Neonatal overfeeding by small‐litter rearing sensitises hippocampal microglial responses to immune challenge: Reversal with neonatal repeated injections of saline or minocycline. (16th November 2017) - De Luca, S. N.; Ziko, I.; Dhuna, K.; Sominsky, L.; Tolcos, M.; Stokes, L.; Spencer, S. J.
Abstract: The early‐life period is extremely vulnerable to programming effects from the environment, many of which persist into adulthood. We have previously demonstrated that adult rats overfed as neonates have hypothalamic microglia that are hyper‐responsive to an immune challenge, as well as hippocampal microglia that respond less efficiently to learning. We therefore hypothesised that neonatal overfeeding would alter the ability of hippocampal microglia to respond to an immune challenge with lipopolysaccharide (LPS) and that concomitant minocycline, a tetracycline antibiotic that suppresses microglial activity, could restore these responses. We induced neonatal overfeeding by manipulating the litter sizes in which Wistar rat pups were raised, so the pups were suckled in litters of four (neonatally overfed) or 12 (control‐fed). We then examined the hippocampal microglial profiles 24 hour after an immune challenge with LPS and found that the neonatally overfed rats had dramatically increased microglial numbers in the hippocampus after immune challenge compared to control‐fed rats. Attempts to reverse these effects with minocycline revealed repeated that neonatal injections, whether with minocycline or with saline, markedly suppressed microglial number and density throughout the hippocampus and abolished the difference between the groups in their responses to LPS. These data suggest that neonatal overfeeding not only can have lasting effects on hippocampal immune responses, but also that neonatal exposure to a protocol of repeated injections, irrespective of treatment, has a pronounced long‐term impact, highlighting the importance of considering these effects when interpreting experimental data.